The Way of Reconciliation: Review of Gavin Van Horn, The Way of Coyote: Shared Journeys in the Urban Wilds - Gigliotti, Carol (Humanimalia, 2020)
Gavin Van Horn, The Way of Coyote: Shared Journeys in the Urban Wilds. Chicago: University of Chicago Press. 2018. 234 pp. $25.00 (hc).